SUSTAINABLE DEVELOPMENT GOAL: GENDER EQUALITY FOR WOMEN’S EMPOWERMENT AND HUMAN RIGHTS - Kumar Pathania, Sudershan (International Journal of Research -GRANTHAALAYAH, 2017)
Empowerment of women and girls is to be realized through sustainable development. Sustainable development depends on an equitable distribution of resources and it cannot be achieved without gender equality. Gender Equity is the process of allocating resources, programs, and decision making fairly to both males and females without any discrimination on the basis of sex…and addressing any imbalances in the benefits available to males and females. Diane Elson, an adviser to UN Women, argues in her contribution that "the disproportionate responsibility that women bear for carrying out unpaid work is an important constraint on their capacity to realize their rights... Both women and men need time to care for their families and communities, and time free from such care." Women’s empowerment is a key factor for achieving sustainability. Sustainable development and sustainability have various meaning .Sometime it may be equitable distribution of resources and opportunities or living within the limits or sometime it may be defined as understanding the interconnections among economy, society, and environment. Sustainable development is based on the principles of democracy and the rule of law and respect for fundamental rights including freedom and equal opportunities for all. Sustainability cannot exist without equity in the distributional process. Women and girls are crucial contributors, implementers and beneficiaries of sustainable development. At the Sustainable Development Summit on 25 September 2015, UN Member States adopted the 2030 Agenda for Sustainable Development, which includes a set of 17 Sustainable Development Goals (SDGs) to end poverty, fight inequality and injustice, and tackle climate change by 2030. Women’s empowerment through gender equality is a cross-cutting development issue, and unless addressed in multidimensional way, gender equality will not become a reality. Women’s contribution to sustainable development must be recognized. Women have a strong role in education and socializing their children, including teaching them care and responsibility. In order to build women as catalyst for sustainable development, their role in family, community and society at large has to free from socio-cultural and religious traditions that prevent women participation. The secondary data will be used for this paper. The objective of this paper is to highlights the essentials of women contribution in sustainable development as partner and beneficiaries.